1985
DOI: 10.1007/bf00499122
|View full text |Cite
|
Sign up to set email alerts
|

A second polymorphic lens crystallin (LEN-2) in the mouse: Genetic and biochemical analysis of LEN-1 and LEN-2

Abstract: Two electrophoretic polymorphisms affecting lens crystallins, designated LEN-1 and LEN-2, have been discovered among inbred strains of mice. Analysis by isoelectric focusing demonstrated that both crystallins are monomeric proteins with isoelectric points at or above pH 7. Both proteins eluted in the low molecular weight (LM) fraction upon Sephadex G-200 gel filtration but LEN-2 was shown to be larger than LEN-1 by G75SF gel filtration and denaturing gel electrophoresis. Linkage analysis demonstrated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Previous studies of mouse lens crystallins by analytical isoelectric focusing had identified inherited polymorphisms among LM crystallins, one of which was encoded by a locus, Len-l, on chromosome 1 (Skow, 1982;Skow et al, 1985). Biochemical studies indicated that LEN-1 was a gamma crystallin but did not establish whether the electrophoretic polymorphism originated from amino acid substitution or posttranslational modification of a gamma crystallin polypeptide.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies of mouse lens crystallins by analytical isoelectric focusing had identified inherited polymorphisms among LM crystallins, one of which was encoded by a locus, Len-l, on chromosome 1 (Skow, 1982;Skow et al, 1985). Biochemical studies indicated that LEN-1 was a gamma crystallin but did not establish whether the electrophoretic polymorphism originated from amino acid substitution or posttranslational modification of a gamma crystallin polypeptide.…”
Section: Discussionmentioning
confidence: 94%
“…The mouse gamma crystallin genes have recently been mapped with respect to each other and eye lens obsolescence (Elo) (Quinlan et al, 1987) but have not been positioned relative to other gene markers on chromosome 1. An inherited electrophoretic polymorphism in a gamma crystallin polypeptide, designated Len-1, has been located on mouse chromosome 1 about 5 cM distal to Idh-1 (Skow, 1982;Skow et al, 1985) and closely linked to the fibronectin locus (Skow et al, 1985). In this communication, we further examine the linkage relationships of the gamma crystallin gene family to four other gene markers, including Len-1, in the centromerie portion of mouse chromosome 1.…”
Section: Introductionmentioning
confidence: 96%